Instructional Leadership Practices for Developing the 21st Century Competencies of Undergraduate Students at Public Universities in Tanzania - Mushi, Emmanuel Paul; Ye, Yan (Scholar: Human Sciences, 2021)
The purpose of this paper was to identify key instructional leadership (IL) practices and the 21st century competencies (TFCC) and relate the two using the context of Tanzanian public universities. The paper relied on literature review and content analysis to come with survey questionnaire. From literature review and content analysis, thirteen (13) instructional leadership practices and six (6) 21st century competencies were identified. These included leadership focus on improvement of teaching and learning, use of appropriate leadership styles and competencies, and setting vision, mission and goals. Further, the practices included use of social-constructivist instructional methods such as student-centered approach, collaborative learning and problem-based learning. Survey questionnaire formed from the identified IL practices and TFCC was used to collect data from 222 public university lecturers in Tanzania. Analysis of the data though Pearson Correlation r indicated that there is a strong positive relationship between the instructional leadership (IL) practices and the 21st century competencies (TFCC). The analysis found a Pearson Coefficient (r) of .654, with a p-value of .000. Moreover, all the sub-variables under the instructional leadership correlated positively with sub-variables under the 21st century competencies, and there was on average strong positive association of the sub-variables within the two main variables.